KH Ahmad Dahlan’s Teachings: Foundation of Muhammadiyah Educational Philoshopy: Ajaran KH. Ahmad Dahlan: Landasan Filsafat Pendidikan Muhammadiyah - Hidayanto, Anang; Hikmatiyar, Achmad; Huda, Sholihul (Universitas Muhammadiyah Sidoarjo, 2024)
The roots of Muhammadiyah Educational Philosophy are not from the personality of KH. Ahmad Dahlan and his journey in establishing and running the Muhammadiyah organization, especially in the field of education. In writing Muhammadiyah Educational Philosophy has not yet reached the final, but the spirit of Muhammadiyah educational philosophy is reflected in the personality and principles that have been instilled by KH Ahmad Dahlan. Muhammadiyah, which promotes progressive and character education, makes Muhammadiyah education have its own characteristics which become an attraction among the people. The purpose of this writing is to explore the understanding and foundation of the educational teachings of KH Ahmad Dahlan as the root of Muhammadiyah's Educational Philosophy. In collecting information, the author uses library instruments to produce the correct data. In this paper it is concluded that the Muhammadiyah Educational Philosophy is an Islamic educational philosophy which examines the goals and ideals of Muhammadiyah educational institutions which are based on Islamic sources, namely the Qur'an and As Sunnah and are principled from the personality and journey of KH Dahlan in establishing and carry out Muhammadiyah education. Highlights: Muhammadiyah's Educational Philosophy, rooted in KH Ahmad Dahlan's principles, prioritizes Islamic sources for progressive and character-focused education. Evolving under KH Ahmad Dahlan's spirit, it relies on thorough research for development. Distinguished by its Islamic values, it offers a holistic educational approach, appealing to those seeking a unique perspective. Keywords: Education Philosophy, Muhammadiyah, Progressive Education